2012
DOI: 10.1158/1541-7786.mcr-12-0351
|View full text |Cite
|
Sign up to set email alerts
|

SINE Retrotransposons Cause Epigenetic Reprogramming of Adjacent Gene Promoters

Abstract: Almost half of the human genome and as much as 40% of the mouse genome is composed of repetitive DNA sequences. The majority of these repeats are retrotransposons of the SINE and LINE families, and such repeats are generally repressed by epigenetic mechanisms. It has been proposed that these elements can act as methylation centers from which DNA methylation spreads into gene promoters in cancer. Contradictory to a methylation center function, we have found that retrotransposons are enriched near promoter CpG i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 40 publications
2
66
0
Order By: Relevance
“…This hypothesis does not account for some of the peculiarities of the process, such as genomic specificity. Studies have shown that the affected genes can be predicted to some extent using genomic features such as nearby retrotransposon density (48) (a high density is associated with fewer changes with age), occupancy by polycomb group pro teins in embryonic cells (33) (with polycomb group targets showing more agerelated changes), direct association with specific genomic sequences (49), and inverse association with CTCF binding sites (50). Additionally, baseline gene expression is also likely to influ ence this process (51).…”
Section: Mechanisms Of Dna Methylation Driftmentioning
confidence: 99%
“…This hypothesis does not account for some of the peculiarities of the process, such as genomic specificity. Studies have shown that the affected genes can be predicted to some extent using genomic features such as nearby retrotransposon density (48) (a high density is associated with fewer changes with age), occupancy by polycomb group pro teins in embryonic cells (33) (with polycomb group targets showing more agerelated changes), direct association with specific genomic sequences (49), and inverse association with CTCF binding sites (50). Additionally, baseline gene expression is also likely to influ ence this process (51).…”
Section: Mechanisms Of Dna Methylation Driftmentioning
confidence: 99%
“…16,17 Aside from direct disruption via insertion within genes, mobilized TEs can exert position effects on loci near the site of integration by disrupting normal mechanisms of regulated expression. 18 In some cases, TE-initiated transcription can proceed through neighboring loci, leading to the generation of chimeric transcripts that may actively promote neoplastic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…86 Inclusion of mouse SINE B1 elements or Alu sequences upstream of reporter gene promoters led to increased gene repression and epigenetic modifications with time, though the SINE copies were unmethylated. 87 A particular mouse SINE B2 element and a subfamily of mouse SINE B1 were found to function as boundary elements that influenced dynamic changes in chromatin and transcriptional regulation, which required simultaneous RNA polymerase III sense transcription and RNA polymerase II antisense transcription of the SINE or the transition from RNA polymerase III transcription to RNA polymerase II transcription of the same DNA strand of the SINE, respectively. 88,89 Recent high throughput sequencing of human and mouse transcription start sites (TSSs) identified that retrotransposon TSSs comprised a surprisingly large percentage of total TSSs, ∼3%-8% and ∼2%-4%, in different tissues from humans and mice, respectively.…”
Section: Consequences Of Ongoing Retrotransposition In Mammalsmentioning
confidence: 99%